Synthesis, characterization and thermal behaviour of solid 2-methoxycinnamylidenepyruvate of some bivalent metal ions in CO2 and N2 atmospheres - Carvalho, C. T. de; Siqueira, A. B.; Ionashiro, E. Y.; Ionashiro, Massao [UNESP] (Editora Unesp, 2010)
Compostos M-2-MeO-CP foram sintetizados no estado sólido, onde M representa os metais bivalentes (Mn(II), Fe(II), Co(II), Ni(II), Cu(II) e Zn(II)) e 2-MeO-CP é o 2-metoxicinamalpiruvato. Para estabelecer a estequiometria e estudar o comportamento térmico desses compostos foram utilizadas termogravimetria, análise térmica diferencial simultânea (TG-DTA), calorimetria exploratória diferencial (DSC), análise elementar e complexometria com EDTA. Os resultados foram concordantes com a fórmula geral: M(L)2∙H2O. em ambas as atmosferas a decomposição térmica ocorre em etapas consecutivas e é característica de cada composto. em atmosfera de CO2 os resíduos finais foram: Mn3O4, Fe3O4, Co3O4, NiO, Cu2O e ZnO, enquanto que em atmosfera de N2 a decomposição térmica ainda é observada até 1000 ºC.

Solid State M-2-MeO-CP compounds, where M stands for bivalent metals (Mn, Fe, Co, Ni, Cu and Zn) and 2-MeO-CP is 2-methoxycinnamylidenepyruvate, were synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), elemental analysis and complexometry were used to establish the stoichiometry and to study the thermal behaviour of these compounds in CO2 and N2 atmospheres. The results were consistent with the general formula: M(L)2∙H2O. In both atmospheres (CO2, N2) the thermal decomposition occurs in consecutive steps which are characteristic of each compound. For CO2 atmosphere the final residues were: Mn3O4, Fe3O4, Co3O4, NiO, Cu2O and ZnO, while under N2 atmosphere the thermal decomposition is still observed at 1000 º C.
Keywords: bivalent metals; 2-methoxycinnamylidenepyruvate; thermal behaviour; CO2; N2